Collective values in an entrepreneurial world: imagining craft labour in cultural work. (1st April 2018) - ,
Abstract : Established entertainment industry unions are often perceived to be in decline in a new landscape of work that requires new forms of organising, but the International Alliance of Theatrical Stage Employees and Allied Crafts (IATSE), a union that represents precarious workers in the entertainment industries in North America continues to expand its membership. This article analyses a shift from seniority-based to skill-based hiring practices in IATSE locals that began in the mid-1990s. Case study research on the formation of a skill-based Canadian IATSE local in 1998 finds that skill-based and seniority-based hiring are each representative of different conceptions of labour. However, the picture this case study sketches also suggests that these seemingly opposing concepts of labour – skill-based and seniority-based – are entangled. The idea of hiring based on 'skill' proved to be an effective organising strategy, but intensified precarious working conditions for IATSE employees, and relied on a more entrepreneurial conception of labour.